2013
DOI: 10.1111/mmi.12315
|View full text |Cite
|
Sign up to set email alerts
|

Replication arrest is a major threat to growth at low temperature in Antarctic Pseudomonas syringaeLz4W

Abstract: SummaryChromosomal damage was detected previously in the recBCD mutants of the Antarctic bacterium Pseudomonas syringae Lz4W, which accumulated linear chromosomal DNA leading to cell death and growth inhibition at 4°C. RecBCD protein generally repairs DNA double-strand breaks by RecA-dependent homologous recombination pathway. Here we show that ΔrecA mutant of P. syringae is not cold-sensitive. Significantly, inactivation of additional DNA repair genes ruvAB rescued the cold-sensitive phenotype of ΔrecBCD muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…These data indicate that, despite the increased solubility of ROS at low temperature, it is unlikely that oxidative stress caused by ROS was the main cause of DNA damage at low temperature. However, replication fork arrests and fork damage might be exacerbated at low temperature due to DNA secondary structures and DNA‐protein complexes becoming more stable (Sinha et al ., ). Because stalled replication forks can be repaired by DSB and HR allowing replication to proceed (Kuzminov, ; Cox et al ., ), the data suggest that the increase in DNA repair and protection proteins relates to overcoming stalled DNA replication that would otherwise cause growth arrest, rather than a response to oxidative damage.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that, despite the increased solubility of ROS at low temperature, it is unlikely that oxidative stress caused by ROS was the main cause of DNA damage at low temperature. However, replication fork arrests and fork damage might be exacerbated at low temperature due to DNA secondary structures and DNA‐protein complexes becoming more stable (Sinha et al ., ). Because stalled replication forks can be repaired by DSB and HR allowing replication to proceed (Kuzminov, ; Cox et al ., ), the data suggest that the increase in DNA repair and protection proteins relates to overcoming stalled DNA replication that would otherwise cause growth arrest, rather than a response to oxidative damage.…”
Section: Resultsmentioning
confidence: 99%
“…If the energy threshold for the bactericidal effect is lower than the energy threshold for suppression of the recovery system, the synergistic bactericidal effect may not be observed. A recent study found that cold stress, which has a strong association with oxidative stress (36) increases the bactericidal effect of UVC irradiation (37). Furthermore, the simultaneous use of UVC irradiation and ozone increased the E. coli bactericidal level higher than that of the individual treatments, which was dependent on the generation of hydroxyl radicals (38).…”
Section: P<005mentioning
confidence: 97%
“…It was found that, at low temperatures, the DNA replication fork frequently encounters barriers that halt its progression, leading to the formation of secondary structures that are recognized by a nuclease that causes linearization of the chromosome, which compromises cell survival. The helicase activity of the RecBCD enzyme is able to prevent this, facilitating the re-initiation of DNA replication (Sinha et al, 2013). In addition, RNase R, a very processive exoribonuclease that degrades highly structured RNA, appears to be essential for the growth of P. syringae Lz4W (Purusharth et al, 2007) and P. putida (Reva et al, 2006;Fonseca et al, 2008) at low temperatures.…”
Section: Influence Of Low Temperature On Dna Replication Dna Transcrmentioning
confidence: 99%